2021
DOI: 10.1186/s13640-021-00548-4
|View full text |Cite
|
Sign up to set email alerts
|

An overview of touchless 2D fingerprint recognition

Abstract: Touchless fingerprint recognition represents a rapidly growing field of research which has been studied for more than a decade. Through a touchless acquisition process, many issues of touch-based systems are circumvented, e.g., the presence of latent fingerprints or distortions caused by pressing fingers on a sensor surface. However, touchless fingerprint recognition systems reveal new challenges. In particular, a reliable detection and focusing of a presented finger as well as an appropriate preprocessing of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 66 publications
(47 citation statements)
references
References 49 publications
0
40
0
Order By: Relevance
“…In the last decade, researchers have developed touchless approaches which eliminate these problems. These innovations, however, come with new issues, mainly centered around incompatibility with (established) touch-based fingerprinting and the problem of detecting fakes reliably; see Priesnitz et al (2021) for a review of touchless fingerprinting projects.…”
Section: Technological Challengesmentioning
confidence: 99%
“…In the last decade, researchers have developed touchless approaches which eliminate these problems. These innovations, however, come with new issues, mainly centered around incompatibility with (established) touch-based fingerprinting and the problem of detecting fakes reliably; see Priesnitz et al (2021) for a review of touchless fingerprinting projects.…”
Section: Technological Challengesmentioning
confidence: 99%
“…It can also be observed that a more convenient and practically relevant recognition process is increasingly becoming the focus of research. For a comprehensive overview on the topic of contactless fingerprint recognition, including publications which consider only parts of the recognition pipeline, the reader is referred to [ 19 , 20 ].…”
Section: Related Workmentioning
confidence: 99%
“…Fingerprint scanner is a sensor that will be used as a biometric recognition sensor (Priesnitz et al, 2021) in the form of fingerprint from the unlock.…”
Section: Fingerprint Sensormentioning
confidence: 99%